(untitled) (Journal of Student Affairs in Africa, 2023)
Student counselling centres are struggling to meet the demand for mental health services, which has intensified in recent years. The increased need for mental health services often needs to be managed with limited resources, posing numerous challenges to addressing the demand for mental health support. This challenge calls for innovative ways to address the mental health needs of students and optimise the limited resources available. During the Covid-19 pandemic the peer helpers at Emthonjeni Student Wellness at Nelson Mandela University, in collaboration with the programme coordinator, introduced innovative psycho-educational workshops, virtually, to support students. In reflecting on our journey, we realise our peer helpers were at the forefront of mental health prevention initiatives at a time when many of our students were in dire need of support. The content discussed in the workshops offered valuable insights and tips and these tips could be applied, by participating students, before their mental health deteriorated. These peer-led initiatives expanded our reach and capacity during a period of great stress brought by the Covid-19 pandemic, and they will continue to do so beyond the pandemic. This reflective paper shares the details of our virtual workshops and the insights gained from the process.